PRELIMINARY INDICATION OF RESISTANT ON SENGON (Falcataria moluccana) FROM PAPUA PROVENANCE TO GALL RUST DISEASE - M Charomaini Z; Burhan Ismail (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2008)
Gall rust disease infected Falcataria moluccana plantations, in several locations in East and Central Java. Effort to eradicate the disease using fungicidal treatment not effective at operational scale. One of the techniques to solve the problem is to develop rust resistant genotypes by selecting tolerant individuals in the field. Kediri is the area where the gall rust disease was found with high level invasion therefore the selection was conducted. The research area is a provenance and progeny trial which was established using 6 replications or blocks, each block contained 77 families, (37 families are collected from Candiroto, 20 from Kediri, 15 from Lombok and 5 from Papua). Result from the data analysis found that individuals from several provenances of Waga-waga, Kuaulu; Muai, Wamena; Hubikosi; Muliama Bawah, Asologoima of Papua, Irian Jaya appeared to be more tolerant to the gall rust diseases than others.